A new mutation in the CSB gene in a Chinese patient with mild Cockayne syndrome. Issue 2 (7th February 2014) - Luo, Yu; Ling, Yan; Chen, Jiachao; Xu, Xi; Chen, Chen; Leng, Fei; Cheng, Jing; Chen, Min; Lu, Zhiqiang
Key Clinical Message Cockayne syndrome (CS) is a rare autosomal recessive genetic disease characterized by growth failure and progressive neurological degeneration. Here we report a mild form of CS patient who was homozygous for the C526T transition resulting in a new nonsense mutation, which converts Arg176 to a stop codon.